2009
DOI: 10.1248/bpb.32.55
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of (-)-Epigallocatechin-3-gallate on Aging Mice Induced by D-Galactose

Abstract: Aging is a complicated multifactorial process in which a progressive decline in the physiologic function of organisms occurs. Oxidative stress and reactive oxygen species (ROS) have been proposed to be major cause of aging and other aging-related neurodegenerative conditions such as Alzheimer's disease.1,2) Aging-related oxidative damage in the brain and memory impairment mainly result from an imbalance between ROS generation and antioxidant enzyme activities. The overproduction of ROS or decrease in antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
73
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 35 publications
7
73
1
Order By: Relevance
“…The present results are in accordance with the results in which EGCG increased SOD content and protected against glycation end products induced neurotoxicity by decreasing ROS and MDA [75]. Results are also in agreement with the results showed that EGCG treatment led to increase in SOD content and decrease in MDA in the hippocampus [76]. In addition, EGCG is able to bind Aβ; it may act as an antioxidant and anti-inflammatory against Aβ aggregation in hippocampus and thus have a neuroprotective effect.…”
Section: Discussionsupporting
confidence: 92%
“…The present results are in accordance with the results in which EGCG increased SOD content and protected against glycation end products induced neurotoxicity by decreasing ROS and MDA [75]. Results are also in agreement with the results showed that EGCG treatment led to increase in SOD content and decrease in MDA in the hippocampus [76]. In addition, EGCG is able to bind Aβ; it may act as an antioxidant and anti-inflammatory against Aβ aggregation in hippocampus and thus have a neuroprotective effect.…”
Section: Discussionsupporting
confidence: 92%
“…In order to protect cells against oxidative damage induced by free radicals, endogenous antioxidant enzymes such as CAT, SOD, and GPx are activated in the body. As there is a strong correlation between oxidative stress and cognitive dysfunction, these antioxidant enzymes have important roles in fixing memory and learning deficits (7,8). In our study, decreased levels of SOD, GPx, and CAT were observed in D-galactose-treated mice.…”
Section: Discussionsupporting
confidence: 52%
“…When it is present at higher levels than normal, it can be converted to galactitol by galactose oxidase, resulting in the generation of oxygen-derived free radicals (6). Chronic systemic exposure to D-galactose induces aging-related changes such as corruption of spatial learning, memory loss, neurodegeneration, and diminishing activities of antioxidant enzymes and increased production of free radicals (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has convinced many researchers that oxidants play an important role in aging. Chronic administration of a low dose of D-galactose (D-gal) induces changes that resemble natural aging in animals [13][14][15][16][17][18][19][20] . D-galactose is a physiological nutrient obtains from lactose in milk.…”
Section: Introductionmentioning
confidence: 99%